Intravenous Push Administration of Antibiotics: Literature and Considerations. (June 2018) - Spencer, Samantha; Ipema, Heather; Hartke, Patricia; Krueger, Courtney; Rodriguez, Ryan; Gross, Alan E.; Gabay, Michael
Intravenous (IV) push administration can provide clinical and practical advantages over longer IV infusions in multiple clinical scenarios, including in the emergency department, in fluid-restricted patients, and when supplies of diluents are limited. In these settings, conversion to IV push administration may provide a solution. This review compiles available data on IV push administration of antibiotics in adults, including preparation, stability, and administration instructions. Prescribing information, multiple tertiary drug resources, and primary literature were consulted to compile relevant data. Several antibiotics are Food and Drug Administration–approved for IV push administration, including many beta-lactams. In addition, cefepime, ceftriaxone, ertapenem, gentamicin, and tobramycin have primary literature data to support IV push administration. While amikacin, ciprofloxacin, imipenem/cilastatin, and metronidazole have limited primary literature data on IV push administration, available data do not support that route. In addition, a discussion on practical considerations, such as IV push best practices and pharmacodynamic considerations, is provided.